Depletion of langerin+ cells enhances cutaneous wound healing. Issue 4 (15th May 2020) - Rajesh, Aarthi; Stuart, Gabriella; Real, Nicola; Ahn, Jenny; Tschirley, Allison; Wise, Lyn; Hibma, Merilyn
Summary: Langerin is a C‐type lectin receptor that is expressed on Langerhans cells and langerin‐positive dermal dendritic cells in the skin. Little is known about the function of langerin + cells in wound healing. In this study, the effects of ablation of langerin + cells on healing of a full‐thickness excision wound were investigated using the langerin‐DTR depletable mouse. Strikingly, depletion of langerin + cells resulted in more rapid reduction in wound area. Accelerated wound healing in the langerin + ‐cell‐depleted group was characterized by enhanced neo‐epidermis and granulation tissue formation, and increased cellular proliferation within the newly formed tissues. Accelerated healing in the absence of langerin + cells was associated with increased levels of granulocyte–macrophage colony‐stimulating factor, F4/80 + cells and blood vessels within the granulation tissue. These data support an inhibitory role for langerin + cells during wound healing. Therapies that suppress langerin + cells or their function may therefore have utility in progressing the healing of wounds in humans. Abstract : Ablation of langerin‐positive cells in the langerin‐DTR depletable mouse accelerates healing of a full‐thickness cutaneous wound. Neo‐epidermis and granulation tissue formation was increased, associated with increased cellular proliferation, F4/80‐positive cell infiltration, GM‐CSF production and granulation tissue vascularization. These data provide evidence of a diverse role for langerin‐positive cells in the regulation of wound healing.